Pseudomonas aeruginosa in Chronic Lung Infections: How to Adapt Within the Host? - Faure, Emmanuel; Kwong, Kelly; Nguyen, Dao (Frontiers in Immunology, 2018)
Bacteria that readily adapts to different natural environments, can also exploit this versatility upon infection of the host to persist. Pseudomonas aeruginosa, a ubiquitous Gram-negative bacterium, is harmless to healthy individuals, and yet a formidable opportunistic pathogen in compromised hosts. When pathogenic, P. aeruginosa causes invasive and highly lethal disease in certain compromised hosts. In others, such as individuals with the genetic disease cystic fibrosis, this pathogen causes chronic lung infections which persist for decades. During chronic lung infections, P. aeruginosa evolves and adapts to the host environment towards a state of reduced bacterial invasiveness that favours bacterial persistence without causing overwhelming host injury. Host responses to chronic P. aeruginosa infections are complex and dynamic, ranging from vigorous activation of innate immune responses that are ineffective at eradicating the infecting bacteria, to relative host tolerance and dampened activation of host immunity. This review will examine how P. aeruginosa subverts host defenses and modulates immune and inflammatory responses during chronic infection. This dynamic interplay between host and pathogen is a major determinant in the pathogenesis of chronic P. aeruginosa lung infections.